Klorofil-a dan kaitannya terhadap Produktifitas Primer Perairan Laut Banda pada Fenomena La Nina - Uneputty, Brian Abraham Salmon; Tubalawony, Simon; Noya, Yunita Anganetjie (Politeknik Negeri Sambas, 2022)
The Banda Sea waters are open waters that have very complex dynamics and water characteristics. Those waters have a diverse underwater topography and are surrounded by many islands, both large and small. In addition, these waters are also strongly influenced by the ENSO phenomenon. The purpose of this study was to analyze the distribution pattern of chlorophyll A in marine waters during the La Nina period and the level of primary productivity. This study uses monthly chlorophyll-a data in 2010, from the MODIS AQUA satellite which is then processed using Surfer-12 software. The results showed that there was a pattern of variation in the distribution of chlorophyll-a in the Banda Sea during the El Nino and La Nina phenomena.